HAK ASASI MANUSIA DAN KEBEBASAN BEREKSPRESI DI INDONESIA - Trie Rahmi Gettari; Wira Okta Viana; Meydianto Mene (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Freedom of expression is the right to seek, receive, disseminate information. Through the recognition of the rule of international law in the Universal Declaration of Human Rights (DUHAM), which in Article 19 states that everyone has the right to freedom to have and express opinions, without interference and to seek, receive and express information and opinions in any way and in the absence of restrictions. Freedom of expression in Indonesia today should be questioned for its implementation considering that there are many problems that occur now, one of which is the silencing of freedom of expression, keep in mind that freedom can basically be limited in accordance with the provisions contained in the human rights law and other provisions. Changes to a constitution require the right time, namely when the articles in the constitution are felt to be no longer in accordance with the developments and needs that exist in society, and when the community has begun to feel that there is no guarantee of legal certainty. The existence of the concept of human rights, including the right to freedom of expression and opinion, is closely related to the concept of the state of law. The goal of democracy is the formation of a political life characterized by democracy.Keywords: Freedom of Expression, Democracy, Human Rights